(untitled) (Journal of Namibian Studies : History Politics Culture, 2023)
This research was based on a universal fact: the impossibility of isolating the natural environment of any region In the world from Its regional surroundings, the harnessed winds and clouds between heaven and earth, and the sending winds that stir clouds that spread them in the sky and then make them fragments so you see the rain emerge from within them, evidence of the fluency of the Almighty and the inability of a man to prevent climate changes, and that all he can do is mitigate the effects of these changes. The research was concerned with the statement of several purposes, the most important of which are: 1. View the Geoenvironmental map of the Tabuk region from the following aspects: location, area, borders, population activity, terrain, the most important tourist destinations, and the regional ocean. 2. Definition of the natural environment and the ecosystem and mention the elements and components of the natural environment from the atmosphere, soil, and energy. 3. Highlight the problems and threats to the natural environment with the definition of each problem and the statement of Its effects, focusing in particular on pollution, climate change, and the lack of carbon neutrality. 4. Programs and plans that can be taken to confront environmental variables and climate change, where the research proposed nine programs for this confrontation. 5. Scientific concept of the terms environment and climate change, the research was concerned with the definition of pollution and mentioned pollutants for air, water, terrestrial soil, and agricultural soil, and the research was also Interested in providing a brief definition of each of environmental degradation, environmental disaster, depletion of Natural Resources, ozone layer, acid rain, sewage treatment, sludge, waste, carbon dioxide, atmosphere, black carbon, global warming, heat islands, desertification, extinction of living, soil drift and dredging, fertilizers, and chemical fertilizers. 6. Environmental challenges and risks from the Islamic and systemic perspectives, and within the framework of this purpose, the research is concerned with the following: 1) Islamic Sharia view of environmental challenges and risks. 2) Systemic/legal view of environmental challenges and risks. 3)The totality of environmental challenges and risks, represented by: the ecological imbalance of the planet, the constant decrease in food products, and the deterioration of human, animal, and plant health. 7. Mechanisms for the protection of the natural environment from Islamic and systemic perspectives. The research was interested in explaining two main tools developed by the Islamic Sharia for environmental protection, namely: the mandatory and voluntary legislative mechanism, and the executive mechanism included in the guarantee of waste. In his statement about these two mechanisms, the researcher was interested in mentioning the evidence of the necessity of action for each mechanism, he then concluded his speech on the Sharia mechanism by deriving some of the Sharia provisions from the total Fiqh rules that he inferred. In addressing the mechanisms of environmental protection from the Statutory/legal perspective, the research focused on talking about the emerging environmental risks and the extent to which they need mechanisms, policies, and programs to address them, and then listed nine Improvised mechanisms to protect the natural environment of the planet. 8. Research was interested in presenting the means and methods adopted by the Kingdom of Saudi Arabia to protect the environment, which varied into two types: international conventions ratified by the Kingdom and became hereby ratified in equality of internal regulations, and the second type is the set of environmental regulations/laws issued by royal decrees, the research dealt with a brief presentation of the following regulations: - The system of conservation of potable water sources. - The system of the Saudi Arabian Agricultural Bank. - Forest and pasture system. - Hunting system for wild animals and birds. - New Environmental Law No. m / 165 dated 19/11/1441 Ah. 9. Conclusion has included the most important result and recommendations. 10. References and sources